Contextualizing socio economic rights in post apartheid South Africa - Pillay, Karrisha (Department of Public Law, 2026)
The UNDP Human Development Report 1994 informs us that "a fifth of the developing world's population goes hungry every night, a quarter lacks afcess to even a basic necessity like safe drinking water, and a third lives in abject poverty - at such a margin of human existence that words simply fail to describe it" .1 From other sources it can be learned that more than 1 billion people in the world today live in poverty, and some 550 million go to bed hungry each night. More than 1.5 billion lack access to clean drinking water and sanitation, some 500 million children do not have access to even primary. education, and approximately one billion adults remain illiterate. 2 Although these statistics reflect the global situation, it is quite obvious that statistics peculiar to South Africa are just as appalling. In fact, it doesn't require statistics to reveal the magnitude of poverty facing the majority of South Africa's citizens. This is a glaring, obvious, undeniable and blatant fact and, as such, desperately needs to be addressed. A natural concomitant of poverty on this magnitude is gross malnutrition, lack of education, low life expectation and sub-standard housing. It is this poverty that embraces, clutches and clings to so many South African people that the hopes and efforts of escape remain an unattainable ideal glimmering in the distant future. But the tragedy is that for many, in fact most, that vision of liberation from poverty will never come. And so life continues, those surrounded by an abundance of wealth, riches and comfort whilst the rest remain trapped within the impregnable circle of poverty striving in a desperate, but futile, attempt to abandon those shackles.